Romowie za murami getta warszawskiego [Roma Behind the Walls of the Warsaw Ghetto] - Wróbel, Karolina (Czas Kultury [Time of Culture], 2016)
Article discusses the presence of the Roma within the Warsaw ghetto, whose fate during the Nazi extermination campaign has tended to be overlooked in literature on the Holocaust. The reflections presented here are an attempt to fill this gap. The author refers in particular to the literature of the personal account of the ghetto and focuses on Roma-Jewish relations. This reveals their ambiguity – the tension between the animosity of the Jews towards the Roma and the community invoked in their shared experiences during the ghettoization.
https://katalog.adlr.link/Record/ai-53-521277